Effects of cellulase and xylanase enzymes mixed with increasing doses of Salix babylonica extract on in vitro rumen gas production kinetics of a mixture of corn silage with concentrate - Abdelfattah Z M Salem; German Buendía-Rodríguez; Mona M M Elghandour; María A Mariezcurrena Berasain; Francisco J Peña Jiménez; Alberto B Pliego; Juan C V Chagoyán; María A Cerrillo; Miguel A Rodríguez (Journal of Integrative Agriculture, 2015)
An in vitro gas production (GP) technique was used to investigate the effects of combining different doses of Salix babylonica extract (SB) with exogenous fibrolytic enzymes (EZ) based on xylanase (X) and cellulase (C), or their mixture (XC; 1:1 v/v) on in vitro fermentation characteristics of a total mixed ration of corn silage and concentrate mixture (50:50, w/w) as substrate. Four levels of SB (0, 0.6, 1.2 and 1.8 mL g−1 dry matter (DM)) and four supplemental styles of EZ (1 μL g−1 DM; control (no enzymes), X, C and XC (1:1, v/v) were used in a 4×4 factorial arrangement. In vitro GP (mL g−1 DM) were recorded at 2, 4, 6, 8, 10, 12, 24, 36, 48 and 72 h of incubation. After 72 h, the incubation process was stopped and supernatant pH was determined, and then filtered to determine dry matter degradability (DMD). Fermentation parameters, such as the 24 h gas yield (GY24), in vitro organic matter digestibility (OMD), metabolizable energy (ME), short chain fatty acid concentrations (SCFA), and microbial crude protein production (MCP) were also estimated. Results indicated that there was a SB×EZ interaction (P<0.0001) for the asymptotic gas production (b), the rate of gas production (c), GP from 6 to 72 h, GP2 (P=0.0095), and GP4 (P=0.02). The SB and different combination of enzymes supplementation influenced (P<0.001) in vitro GP parameters after 12 h of incubation; the highest doses of SB (i.e., 1.8 mL g−1 DM), in the absence of any EZ, quadratically increased (P<0.05) the initial delay before GP begins (L) and GP at different incubation times, with lowering b (quadratic effect, P<0.0001) and c (quadratic effect, P<0.0001; linear effect, P=0.0018). The GP was the lowest (P<0.05) when the highest SB level was combined with cellulose. There were SB×EZ interactions (P<0.001) for OMD, ME, the partitioning factor at 72 h of incubation (PF72), GY24, SCFA, MCP (P=0.0143), and pH (P=0.0008). The OMD, ME, GY24 and SCFA with supplementation of SB extract at 1.8 mL g−1 DM were higher (P<0.001) than the other treatments, however, PF72 was lower (quadratic effect, P=0.0194) than the other levels. Both C and X had no effect (P>on OMD, pH, ME, GY24, SCFA and MP. The combination of SB with EZ increased (P<0.001) OMD, ME, SCFA, PF72 and GP24, whereas there was no impact on pH. It could be concluded that addition of SB extract, C, and X effectively improved the in vitro rumen fermentation, and the combination of enzyme with SB extract at the level of 1.2 mL g−1 was more effective than the other treatments.